(untitled) (CSIAM Transactions on Life Sciences, 2025)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne zoonotic disease caused by severe fever with thrombocytopenia syndrome virus. In recent years, there has been an increasing number of human SFTS cases in central and northeast China. In the study region, Dalian, the number of human cases in years between 2011 and 2019 exhibited recurrent patterns in synchrony with the seasonal temperature variation. Here, we develop a transmission dynamics model to incorporate contact characteristics of animal and human hosts from published literature, and fit the model to historical temperature and human incidence data in our study region to analyze trends in human SFTS incidence and the time trends of SFTS prevalence within the natural tick-host cycle. Our analysis highlights the contributions of the systemic, co-feeding, and transovarial transmission routes, and provides insights for cost-effective public health interventions targeted to reducing transmission in these coexisting transmission pathways.